A Pharmacist-Managed Hydroxyurea Prescribing Protocol Improves Uptake and Optimization among Patients with Sickle Cell Disease - Cameron Roessner; Trudy Sale; Kelsey Uminski; Dawn Goodyear; Natalia Rydz (Advances in Hematology, 2024)
Sickle cell disease (SCD) is a common genetic disorder with potentially serious sequelae that can be effectively treated with hydroxyurea. Despite its favorable benefit-risk profile, hydroxyurea uptake in patients with SCD is low. A pilot study was conducted at the Southern Alberta Rare Blood and Bleeding Disorders (SARBBDs) Comprehensive Care Program between January 2020 and September 2023 to assess the implementation of a pharmacist-led protocol for supporting the uptake of hydroxyurea among eligible patients with SCD and optimizing its dosing. The protocol standardized the prescription, monitoring, dose titration, and patient counselling by a clinic pharmacist. The number of patients enrolled in the SARBBDs program increased from 98 in January 2020 to 168 in 2023. During this period, the proportion of patients on hydroxyurea increased from 37.8% to 62.5%, the proportion of patients on hydroxyurea who were at a maximum tolerated dose (MTD) increased from 35.1% to 63.8%, and the average hemoglobin F level increased from 13.9% to 19.7%. The mean time to reach MTD was 10 months and required eight pharmacist interventions, six laboratory assessments, and three dose increases. Hydroxyurea continuation rates were high, with most discontinuations resulting from loss to follow-up or transition to a transfusion management strategy. This real-world pilot study demonstrated that implementation of a pharmacist-led prescribing and monitoring protocol nearly doubled hydroxyurea uptake and achievement of MTD in patients with SCD managed in a rare blood disorders clinic.